2022
DOI: 10.3390/nu14040856
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbohydrate Intake on Strength and Resistance Training Performance: A Systematic Review

Abstract: High carbohydrate intakes are commonly recommended for athletes of various sports, including strength trainees, to optimize performance. However, the effect of carbohydrate intake on strength training performance has not been systematically analyzed. A systematic literature search was conducted for trials that manipulated carbohydrate intake, including supplements, and measured strength, resistance training or power either acutely or after a diet and strength training program. Studies were categorized as eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 114 publications
1
24
0
Order By: Relevance
“…Our findings contrast and agree with the findings of a recent systematic review by Henselmans et al [47], which found that the majority of studies assessing the effects of acute CHO ingestion on RT performance reported no ergogenic effect. There are differences in study inclusion criteria and outcomes of interest that may explain the differences in our findings.…”
Section: Total Training Session Volumesupporting
confidence: 82%
See 3 more Smart Citations
“…Our findings contrast and agree with the findings of a recent systematic review by Henselmans et al [47], which found that the majority of studies assessing the effects of acute CHO ingestion on RT performance reported no ergogenic effect. There are differences in study inclusion criteria and outcomes of interest that may explain the differences in our findings.…”
Section: Total Training Session Volumesupporting
confidence: 82%
“…We have also conducted various sub-group and meta-regression analyses to control for potential confounders. Nonetheless, there is some agreement in results, as Henselmans et al [47] note that CHO ingestion may be beneficial in some circumstances such as fasted training and higher training volumes (< 10 sets per muscle group). This finding by Henselmans et al [47] agrees with the findings of our current metaanalysis in which CHO ingestion improves RT volume performance for longer session durations (> 45 min) and fast durations (≥ 8 h).…”
Section: Total Training Session Volumementioning
confidence: 89%
See 2 more Smart Citations
“…The metabolic flexibility of skeletal muscle allows it to increase energy supply and provide sufficient “fuel” for contraction [ 64 , 65 ]. The importance of carbohydrate as a fuel source in exercise has been known, and the main source of these carbohydrate is glycogen reserve of skeletal muscle during exercise [ 66 , 67 ]. In addition, skeletal muscle actively secretes myogenic protein to exert autocrine, paracrine or endocrine functions to convey its energy demand to other organs, including adipose tissue, the liver, pancreas, cardiovascular system, brain, bone and skin, thus causing crosstalk [ 68 , 69 ].…”
Section: O -Glcnacylation Is An Essential Metabolic Modulato...mentioning
confidence: 99%